Peri-Operative Takotsubo Cardiomyopathy: A Case Series - Alicia M Kowalski; Jeff Cerny; Spencer Kee; Farzin Goravanchi; Elizabeth Rebello (Global Journal of Anesthesiology - Peertechz Publications, 2015)
Takotsubo Cardiomyopathy (TC) is a reversible, stress-induced, non-ischemic cardiomyopathy associated with temporary weakness of the myocardium and midventricular or apical ballooning [1,2]. Angina, ST abnormalities, elevated troponins, ventricular asynergy, CHF, and decreased EF are all components of TC. The unique finding is that they occur on the absence of CAD [3]. In this case series with IRB approval we report three cases of post-operative cardiac symptoms that all resulted in a diagnosis of TC.